Imposition Of Income Tax On Tiktokers Based On Tax Regulations In Indonesia - Syailendra, Moody Rizqy; Aprilia, Indah; Yuan, Luo (Faculty of Law, Universitas Jenderal Soedirman, 2023)
The virtual world has provided various benefits and new opportunities in various fields of human life. One of these opportunities is through social media. As social media platforms have grown, many people are now changing their careers to become content providers. Beyond just seeking pleasure, Tiktok has given its users a ton of options to earn a living. Creative industry players get enormous opportunities to earn income from Tiktok through the various content they create. Tax responsibilities have emerged for Tiktokers because of the increase in persons switching occupations to become Tiktokers and benefit/earn from Tiktok in Indonesia. This research uses a normative juridical approach with statutory and factual approaches. Based on this research, it can be concluded: First, the imposition of income tax on the Tiktoker profession adheres to a self-assessment system, thus the calculation processes up to reporting are completed directly by the Taxpayer in compliance with the relevant laws and regulations. Tiktokers carry out their job by doing evaluations and advertising things that they have praised. Tiktokers then get rewarded for the review videos he has made and uploaded. This is then what is income or profit for Tiktokers. Tiktokers can be subject to the provisions in Article 21 UUPPh in calculating their Income Tax, where this provision applies to artistic workers and those who do not have an agency, as well as freelancers and private employees.